2011
DOI: 10.1681/asn.2011010031
|View full text |Cite
|
Sign up to set email alerts
|

Bβ15–42 Attenuates the Effect of Ischemia-Reperfusion Injury in Renal Transplantation

Abstract: Renal ischemia-reperfusion contributes to reduced renal allograft survival. The peptide B␤ 15-42 , a breakdown product of fibrin, attenuates inflammation induced by ischemia-reperfusion in the heart by competitively blocking the binding of leukocytes to endothelial VE-cadherin, but whether it could improve outcomes in renal transplantation is unknown. Here, we tested the ability of B␤ to ameliorate the effects of renal ischemic injury during allogenic kidney transplantation in mice. In our renal transplantati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 32 publications
3
35
0
1
Order By: Relevance
“…26 The mice were clamped for 16 (bilateral clamping) or 27 minutes (unilateral clamping). Mice were euthanized at 2 hours, 3 days, or 30 days postsurgery.…”
Section: I/rmentioning
confidence: 99%
“…26 The mice were clamped for 16 (bilateral clamping) or 27 minutes (unilateral clamping). Mice were euthanized at 2 hours, 3 days, or 30 days postsurgery.…”
Section: I/rmentioning
confidence: 99%
“…Interestingly, there was an increased inflammatory infiltrate in fibrinogen Ϫ/Ϫ grafts in transplantation experiments, whereas all groups had equal amounts of intrarenal infiltrate in the I/R model. These data suggest that leukocyte tissue infiltration is not only dependent on the binding of circulating fibrinogen to endothelial cells (1,20,21,38) but also affected by the presence of fibrinogen within the tissue.…”
Section: Discussionmentioning
confidence: 83%
“…Alternatively, it might be a valid strategy to target specific domains of the molecule since many biological functions identified for fibrinogen depend on distinct nonoverlapping epitopes (6). Along these lines, we and others (21,32,38,42) have previously demonstrated that the fibrinogen breakdown product, B␤15-42, has beneficial effects in renal I/R injury. Other domains of fibrinogen might be equally important, and their deletion might aggravate or attenuate I/R injury and inflammation independently of fibrinogen's coagulant function.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations